Research into the application of biodiesel in the transport sector of Lithuania - Lebedevas, Sergejus; Vaicekauskas, Andrius (Transport, 2006)
The material of this publication presents the results of a complex research into the application of standard rapseed methyl ester (RME) and new types of biodiesels produced from waste of vegetable oil and animal fat in the transport sector of Lithuania. The analytical analysis of physical, chemical and thermodynamical properties of biodiesels is performed and its results are evualated during the formation of tasks of experimental motor tests and research into mathematical modelling. Their influence for the paramaters of a working process and exploiting characteristics such as power, fuel economy, reliability and harmful emission of gases is evaluated.First Published Online: 27 Oct 2010